Implementasi Penggunaan Model Project Based Learning (PJBL) Dalam Pembuatan Pestisida Organik Untuk Meningkatkan Kreativitas Dan Hasil Belajar Siswa - Danang Margono; Asep Ginanjar Arip; Anna Fitri Hindriana (Edubiologica: Jurnal Penelitian Ilmu dan Pendidikan Biologi, 2018)
Research   objectives   analyze   the   feasibility,   increase   creativity,   learning outcomes and student responses to project based learning (PjBL) learning models in making organic pesticides.  The results of the study was found that: The PjBL model of making  organic  pesticides  can  develop  students'  creativity.  The  results  of  the significance hypothesis test 0,004<0.05, the initial hypothesis (Ho) is rejected, meaning that there is a difference in the average creativity of students between the experimental class and the control class. The results of the hypothesis test of learning outcomes obtained sig values. 0,000 <0,05 then the initial hypothesis (Ho) is rejected indicating that there are differences in cognitive learning outcomes between the experimental class and the control classKeywords: Project Based Learning (PjBL); Pestisida Organik; Kreativitas